Avaliação da função sexual em mulheres brasileiras: um estudo transversal - Silva, Stéfany Gomes da (Universidade Federal de São Carlos, 2022)
Introduction: The physiological female sexual response is mediated by multiple components that, when impaired, can trigger sexual dysfunction (SD) in this population. SD causes negative impacts on women's quality of life and, although the study on the subject is growing, its prevalence is still growing year by year and information on sexual function in Brazilian women is scarce. Objectives: To evaluate sexual function in Brazilian women and to investigate the prevalence and factors associated with the presence of female sexual dysfunction (FSD) in this population. Methods: The present study used the Female Sexual Function Index (FSFI) questionnaire as a basis for DSF screening, which assesses sexual response based on desire, arousal, vaginal lubrication, sexual satisfaction, orgasm and pain. the questionnaire was made available online and could be answered by women aged 18 years or older and with an active sex life, characterized by sexual activity present within the four weeks prior to participation. Scores <26.55 on the FSFI were considered as the presence of DSF. From In addition, women were divided into two groups, with and without DSF. Comparison between groups was performed using demographic characteristics with the t test for independent samples (continuous variables with normal distribution), the Mann-Whitney test (continuous variables without normal distribution) and the chi-square test (categorical variables). The association between the patient's characteristics and the FSD was based on binomial logistic regression. Results: 621 women participated in the study; the average age of participants was 29.8 (8.9%) years, 274 (44.1%) were married and 305 (49.1%) had higher education. About 31.7% (95% CI = 28.2% – 35.5%) had sexual dysfunction based on the FSFI score. The logistic regression performed showed the practice of physical activity as inversely associated with FSD (OR=0.65; CI 0.45 – 0.92), while urinary incontinence (OR=2.21; CI 1.55 – 3, 16) and menopause increase (OR=4.60; CI 1.62 – 13.1) by 2.2 and 4.6 times, respectively, the chance of occurrence of SD. Conclusion: It is believed that menopause and UI are phenomena that contribute to the development of FSD in Brazilian women, while the practice of physical activity reduces the chances of this dysfunction.
Evaluation of sexual function in Brazilian women: a cross-sectional study
Keywords: Disfunções sexuais fisiológicas; Sexualidade; Prevalência; Saúde da mulher; CIENCIAS DA SAUDE